Penyusunan Laporan Keuangan dengan Menggunakan Sistem Website pada Toko Natasyia Collection - Candy Candy; Isty Rosy Cahyani (Universitas Internasional Batam, 2021)
This program aims to transfer knowledge and techniques in making website-based financial reports at the Natasyia Collection Store so that you can create simple financial statements independently anywhere and anytime. This program approach uses data collection techniques, namely interviews, observation, and documentation. Based on interviews and observations, Natasyia Collection Stores still record financial activities manually using several books because they have not yet prepared financial reports. After implementing website-based financial reporting, Natasyia Collection Stores can quickly master and create simple financial statements. This program plays a positive role in increasing knowledge and abilities in the process of making financial reports.